Governance and performance in UK charities - TANG, JIAWEI (2019)
This study aims to explore the association between governance, performance, and chief executive officer (CEO) compensation in United Kingdom (UK) charities. Existing literature of the link between non-profit performance and governance quality is limited for UK charities. This study uses panel data regression analysis, by investigating 100 UK charities over five years between 2013 and 2018. The data is collected from the Charity Commission. Charity performance is measured by programme expense ratio. The results first indicate that the performance is negatively associated with board size. Second, CEO compensation is positively related to board size and CEO tenure length. The study also considers the impact of several other factors on charity performance, such as board gender diversity, CEO age, CEO tenure and CEO compensation. However, the results are not significant enough to draw conclusions. In addition, the study did not find any impact of board gender diversity, CEO age and charity performance on CEO compensation.